Composability model in a distributed simulation environment for supply chain - Gutiérrez, María de los Milagros (2013)
Distributed simulation become popular through the use of HLA standard and the necessity of sharing resources. Nevertheless composability of model is still a problem to overcome. Many solutions propose the use of ontology and SOA architectures in the context of distributed simulation. This work presents a solution to compose simulation models in the context of supply chain simulation. The proposal presents a network ontology that conceptualizes different aspect to taking into account when a federation for supply chain is developed.